2014
DOI: 10.1074/jbc.m113.495358
|View full text |Cite
|
Sign up to set email alerts
|

A Novel “Oxygen-induced” Greening Process in a Cyanobacterial Mutant Lacking the Transcriptional Activator ChlR Involved in Low-oxygen Adaptation of Tetrapyrrole Biosynthesis

Abstract: Background: ChlR activates the transcription of genes encoding low-oxygen-type enzymes in response to hypoxia in cyanobacteria. Results:The chlR-lacking mutant showed a novel "oxygen-induced" greening process upon exposure to air. Conclusion: The contents of photosystems were correlated well with the chlorophyll contents in the greening process. Significance: Oxygen-induced greening provides a promising alternative system to investigate the biogenesis of photosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Also, it was observed that expression of psbA1 , which encodes the low-oxygen induced D1′ protein, is activated by ChlR [150] . The lack of psbA1 on the other hand did not affect D1 levels, whereas D1 levels were decreased under low-oxygen conditions in mutants lacking either ChlR or the low-oxygen induced tetrapyrrole biosynthesis genes, indicating that the decrease of D1 under these latter conditions is caused by chlorophyll deficiency [150,151] . Other reports in planta implicated tetrapyrrole chromophore biosynthesis as positively correlated with holophytochrome synthesis [152] .…”
Section: Function Of Tetrapyrroles As Signaling Molecules and The Oximentioning
confidence: 85%
See 1 more Smart Citation
“…Also, it was observed that expression of psbA1 , which encodes the low-oxygen induced D1′ protein, is activated by ChlR [150] . The lack of psbA1 on the other hand did not affect D1 levels, whereas D1 levels were decreased under low-oxygen conditions in mutants lacking either ChlR or the low-oxygen induced tetrapyrrole biosynthesis genes, indicating that the decrease of D1 under these latter conditions is caused by chlorophyll deficiency [150,151] . Other reports in planta implicated tetrapyrrole chromophore biosynthesis as positively correlated with holophytochrome synthesis [152] .…”
Section: Function Of Tetrapyrroles As Signaling Molecules and The Oximentioning
confidence: 85%
“…Recently it has been observed that Synechocystis cells lacking ChlR, which is a positive regulator of oxygen-independent tetrapyrrole biosynthesis enzymes, are unable to induce the greening process in the light under low-oxygen conditions [150] . When the greening process is induced in the mutant under oxygen-sufficient conditions which allow oxygen-dependent tetrapyrrole biosynthesis needed for chlorophyll biosynthesis, the chlorophyll content increased concurrently with the other photosystem components [151] . These findings indicate that the levels of tetrapyrroles influence accumulation of the respective tetrapyrrole-requiring protein components to ensure that the complex components are only synthesized if a fully functional complex can be assembled.…”
Section: Function Of Tetrapyrroles As Signaling Molecules and The Oximentioning
confidence: 99%
“…The transcript levels of 23 genes for Chl biosynthesis ( gltX , hemA , hemL , hemB , hemC , hemD , hemE , hemF , hemN , hemJ , chlD , chlH , chlI , gun4 , chlM , chlA I , chlA II , cvrA , por , chlL , chlN , chlB and chlG ) and five genes for photosystems ( psaA , psaB , psaC , psbA2/A3 and psbO ) were examined by semi-quantitative reverse-transcriptase PCR in wild-type and ∆chlR cells grown under aerobic and microoxic conditions. Except for chlA II and hemN , the transcript levels of the other 26 genes were almost the same in wild-type and ∆chlR , irrespective of aerobic and microoxic conditions [ 108 ]. Thus, chlA II , ho2 , hemN and psbA1 may only be the ChlR-targets in Synechocystis 6803.…”
Section: Transcriptional Regulator Chlrmentioning
confidence: 99%
“…Protein concentration was determined by Bradford assay (Protein Assay, Bio-Rad, Hercules, CA) with bovine serum albumin as the standard. Western blot analysis was carried out as described previously 55 . The specific protein bands were visualized by a lumino-image analyzer (LAS-3000mini, Fujifilm, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%